Shibuya Station as a Megastructure: Lessons for Future Urban Mobility - Aranda, Antonio Luque (Journal of Art, Architecture and Built Environment, 2026)
Shibuya Station is regarded as a highly complicated transportation space in modern day Tokyo. The complication stems from overlaying railway networks, underground networks, commercial projects, as well as highly-dense urban environment. Therefore, the current study aimed to analyze Shibuya Station in terms of megastructural assemblage, wherein the spatial arrangement of the station has undergone phases of growth and restructuring. The station was analyzed by performing a qualitative architectural reading of its infrastructural layering, integration of functions, and its connection with the environment in the city. Instead of suggesting a prescriptive model, the research established repetitive space conditions including incremental expansion, compromising of activities, and long-term adaptability, defining big metropolis mobility centers. The study situated Shibuya Station, in the context of the current discussions on the urban movement and large-scale infrastructures, to assume an important part in the critical comprehension of how large transport nodes are formed by dense urban landscapes.